Sea trade port: business-model structure and source of innovation - I. M. Nyenno (Ринкова економіка: сучасна теорія і практика управління, 2018)
The article deals with the structure of the business-model, the complementary assets are described on the case of the sea trade port as a foundation of the business-model creation. The complementary assets use are studied in the context of operational strategies to obtain economic rents in the case of sale; the formation of a joint venture, public-private partnerships; signing the concession lease or licensing rights of access to complementary assets.